Multi-disciplinary optimization of variable rotor speed and active blade twist rotorcraft: Trade-off between noise and emissions - Polyzos, Nikolaos D.; Vouros, Stavros; Goulos, Ioannis; Pachidis, Vassilios (Elsevier, 2020)
The concepts of variable rotor speed and active blade twist are emerging technologies for the next generation of civil rotorcraft. Previous research has focused on the optimum implementation of these technologies for improved fuel economy and environmental impact. Within this work, an integrated approach is deployed to quantify the concurrent reductions in rotor noise and NOx emissions. A relaxation-based free-wake inflow model, coupled with unsteady blade aerodynamics modeling, resolves the flow-field around the main rotor. Aero-acoustic predictions are performed through an acoustic-analogy-based formulation. Gaseous emissions are then predicted via stirred-reactor modeling, coupled with zero-dimensional engine performance analysis method. This strategy is incorporated into a multi-disciplinary genetic algorithm optimization process based on surrogate modeling. Optimal schedules of combined variable rotor speed and active blade twist controls are derived for a twin-engine light helicopter in descent. The accrued schedules suggest NOx reductions between 6% and 21%, simultaneously with source-noise reductions of the order of 2–8 dB, relative to the non-morphing rotor case. The developed strategy constitutes an enabling methodology for the holistic and multi-disciplinary assessment of morphing helicopter rotor configurations.
Keywords: Helicopters; Aerodynamics; Aeroacoustics; Gas turbines; Multi-disciplinary optimization; Environmental impact